PROCESSING OF FISH AND FISH PRODUCTS - Polvonov Xurshid Madaminovich; Mamatkulov Mamatkul Hamroqulovich (Journals Park Publishing, 2022)
Among our people there is a view that white spots arise from eating mixed products of fish, milk, eggs. In fact, what are the causes of the origin of vitiligo disease.
Keywords: fish; milk; eggs